2018
DOI: 10.1080/15476286.2018.1559688
|View full text |Cite
|
Sign up to set email alerts
|

Molecular network of miR-1343 regulates the pluripotency of porcine pluripotent stem cells via repressing OTX2 expression

Abstract: 2019) Molecular network of miR-1343 regulates the pluripotency of porcine pluripotent stem cells via repressing OTX2 expression, RNA Biology, 16:1, 82-92, ABSTRACTPorcine OTX2 was found to be highly activated in porcine iPS cells (piPSCs) that were reported by different laboratories worldwide. To reveal the regulatory function of OTX2 in porcine reprogrammed cells, we screened porcine miRNA-seq databases and found two miRNAs, miR-1343 and miR-545, that could specifically bind to 3ʹUTR of OTX2 and suppress endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…In the ovaries of highly fertile sows, miR-1343 suppresses expression of transforming growth factor-β receptor type 1 (TGFBR1) to inhibit pig granule cell proliferation and promote apoptosis, thus affecting sow fecundity [72]. Furthermore, miR-1343 specifically binds to the 3´UTR of Orthodenticle homeobox 2 (OTX2) and inhibits endogenous OTX2 expression in pig pluripotent stem cells (piPSCs), enhancing the expression of pluripotency genes and thus maintaining piPSCs pluripotency in pigs [73]. Finally, we chose to focus specifically on PGM1, which has the highest expression level in porcine longissimus dorsi and biceps femoris.…”
Section: Discussionmentioning
confidence: 99%
“…In the ovaries of highly fertile sows, miR-1343 suppresses expression of transforming growth factor-β receptor type 1 (TGFBR1) to inhibit pig granule cell proliferation and promote apoptosis, thus affecting sow fecundity [72]. Furthermore, miR-1343 specifically binds to the 3´UTR of Orthodenticle homeobox 2 (OTX2) and inhibits endogenous OTX2 expression in pig pluripotent stem cells (piPSCs), enhancing the expression of pluripotency genes and thus maintaining piPSCs pluripotency in pigs [73]. Finally, we chose to focus specifically on PGM1, which has the highest expression level in porcine longissimus dorsi and biceps femoris.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA miR-1343 has so far been identified to play roles in regulating the fibrosis of human and the pluripotency of porcine pluripotent stem cells [49,50], and some studies showed that miR-1343 was related with the susceptible to porcine reproductive and respiratory syndrome (PRRS) and pig backfat formation [51,52]. So far, no studies clearly reported the function of miR-1343 in pork quality formation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in pigs revealed that miRNAs, including miR-1343, miR-302, miR-302b and miR-200 , are involved in the acquisition and maintenance of cell pluripotency by regulating the expression of TFs, such as SOX2 and OCT-4 ( Ma et al, 2014 ; Qiao et al, 2019 ; Xie et al, 2019 ). However, the impact of miRNAs during cell reprogramming and development of pig SCNT embryos has not been extensively explored.…”
Section: Introductionmentioning
confidence: 99%